Association of two different repetitive DNA elements near immunoglobulin light chain genes. - Wilson, R (1983)
Sequence studies of repetitive DNA elements approximately 6 kb 3' of the mouse immunoglobulin CK region gene show that the R element located there (Gebhard et al. (1982) J. Mol. Biol. 157, 453-471) is adjacent to a 500 base pair long element which shows 80% homology to the BAM5 element sequenced by Fanning (Nuc. Acids Res. (1982), 10, 5003-5013). Neither the BAM5 element nor the R element itself is surrounded by a direct repeat, but the composite element (BAM5 + R) is surrounded by a 15 base pair direct repeat (with one mismatch). Direct repeats, consisting of target site sequences that surround a repetitive DNA element, are thought to arise during the insertion of the element at that site. It therefore appears that the BAM5 and R elements interacted and inserted as a linked entity. The existence of other BAM5/R composites throughout the mouse lambda chain locus indicates that BAM5-R cooperation is not a rare event.